JENIS DAN FUNGSI GAYA BAHASA DALAM PEMAKNAAN KUMPULAN CERPEN KEMBALINYA TARIAN SANG WAKTU: STILISTIKA - Samhudi, Obi; Effendy, Chairil; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractÂ The aims of this research to describe type, meaning and function forms of language, along with implementation of learning types and function of language form in the elucidation of the short story collection Arif Saifun Kojeh toward Indonesian subjects in school. This research specifically examines the belles-lettres that collection short story Kembalinya Tarian Sang Waktu by Arif Saifun Kojeh. The method used is descriptive method and approach that aims to phenomenological stylistics research issues in accordance with the facts. Short story analyzed as nine stories. The result showed the types of language form is most often to arise is personification, metaphor, hyperbole, litotes, and simile. The amount number of language form consist of 81 numbered form as personification, metaphor language form amount to 83, are 39 form of hyperbolic language, the form litotes language totaled 10, and totaled 9 of simile language form. Meaning contained in the short story collection Kembalinya Tarian Sang Waktu by Arif Saifun Kojeh mostly inclined to connotative and denotative containing about advices life, religiosity, social criticism, and romance.The function of language in this short story form in collection Kembalinya Tarian Sang Waktu By Kojeh Arif Saifun is both an aesthetic so that makes every story in this collection short story was interest and fresh.Furthermore, the other function is to enhancing reading and strengthens the idea in literature.Â Keyword: Type, Function, and StylisticsÂ